Risk Factor Analysis of Work Fatigue on Online Motorcycle Taxi Drivers in Jember Region - Laksmi Indreswari; Handhayani Sri Fatika Laraswati; Rony Prasetyo (Journal of Agromedicine and Medical Sciences, 2023)
Fatigue is part of the main problem in workers that can reduce health status resulting in accidents to death. Work fatigue is still the main cause of work accidents, especially for drivers. Online motorcycle taxi drivers are a group at high risk of fatigue because most of their working time is on the road. This study aims to analyze the effect of risk factors on work fatigue on online motorcycle taxi drivers in the Jember Region. The type of this research is observational analytic with cross-sectional design. The sample is 100 respondents. The sampling technique used consecutive sampling method. The research was conducted from February 2021 to April 2021 using a questionnaire. Data analysis using Spearman Correlation test and Logistic Regression test. The results of Spearman's analysis were age (p = 0.000), smoking habits (p = 0.000), work motivation (p = 0.000), years of service (p = 0.000), and length of work (p = 0.002). The results of the Logistics Regression analysis are the length of service (p = 0.000). The conclusion of this study is that age, smoking habits, work motivation, years of service, and length of work have an influence on work fatigue and tenure is the most influential risk factor for online motorcycle taxi drivers in Jember Region. The suggestion of this research is that it is necessary to research other risk factors and other fatigue measurement methods and the driver is expected to reduce the level of risk of work fatigue. Keywords: risk factors, work fatigue, online motorcycle taxi drivers